Sources for studying the Holocaust : a guide - Bartrop, Paul R. (Paul Robert), 1955- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2023)
"Sources for Studying the Holocaust provides a pathway for readers to engage with questions about what sources can be used to study the Holocaust. For many historians the challenge has been how to rescue the story from oblivion when oft-used sources for other periods of history introduce even more issues around authenticity and reliability. What can be learned of what transpired in villages and towns numbering several thousand people, when all its Jewish inhabitants were totally obliterated through Nazi action? Who can furnish eyewitness testimony, if all the eyewitnesses were killed? How does one examine written records preserving knowledge of facts or events, where none were kept or survived the onslaught? And what weight do we put upon such resources which did manage to endure the destruction wrought by the Holocaust? Each chapter looks at one of a diverse range of source material from which scholars have rescued the history, including survivor testimony, diaries, letters, newspaper accounts, photographs, trial documents, artefacts, digital resources, memorials, films, literature and art. Each chapter shows how different types of records can be utilized as accurate sources for the writing of Holocaust history. Collectively, they highlight the ways in which all material, even the most fragmentary, can be employed to recreate a reliable record of what happened during the Holocaust and show how all sources considered can be employed to find meaning and understanding by exploring a range of sources deeply. This book is a unique analysis of the types of sources that can be used to access the history of Holocaust. It will be of invaluable interest to readers, students and researchers of the Holocaust"-- Provided by publisher.
Part 1 : The Personal Domain -- Oral History : Hearing the Voice of the Survivors / Joanna Salapska-Gelleri and Paul R. Bartrop -- Letters : An Intimate and Innocent Window into History / Tyler Hallatt -- Written Remnants of Catastrophe : Holocaust Diaries as Historical Sources / Amy Simon -- Analysing Memoirs : Gone but Not Forgotten / Kayla M. Stanton -- A Thousand Unspoken Words : Reading Photographs of the Holocaust / Joshua Fortin -- Part 2 : The Public Domain -- Considering Nazi Propaganda as a Source for Studying the Holocaust / Paul R. Bartrop -- Using Trial Documents for Holocaust Study / Michael Dickerman -- Understanding Holocaust Memory through Museums and Memorials / Abigail Winslow -- Using Church Documents for Holocaust Study / Michael Dickerman -- Contemporary Newspapers as Sources for Approaching Holocaust Study / Eve E. Grimm -- Using Yiddish Sources in Studying the Holocaust / Freda Hodge -- Researching the Holocaust in a Digital World / Rachel Tait-Ripperdan -- Persistence of Memory through Artefacts / Melissa Minds VandeBurgt and Bailey Rodgers -- Part 3 : The Popular Domain -- Learning about the Holocaust through Movies / Paul R. Bartrop -- How Holocaust Documentaries Defined Documentary Cinema / Yvonne Kozlovsky Golan -- Humanising the Holocaust : Literature as a Source for Studying the Holocaust / Kinsey Brown -- Art as a Source for Studying the Holocaust / Laura Morowitz -- Part 4 : Epilogue -- Thinking About and Using Documents from the Perpetrators / Beth Griech-Polelle -- Chronology of the Holocaust / Paul R. Bartrop
Includes bibliographical references and index.
Keywords: Holocaust, Jewish (1939-1945) -- Historiography; Holocaust, Jewish (1939-1945) -- Study and teaching; Holocaust, Jewish (1939-1945) -- Sources; Historiography; Study skills; 1939-1945; Sources